2018
DOI: 10.1016/j.joen.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel Endodontic Disinfection Approach Using Catalytic Nanoparticles

Abstract: The results reveal the potential to exploit nanocatalysts with enzymelike activity as a potent alternative approach for the treatment of endodontic infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 38 publications
(51 reference statements)
0
21
0
4
Order By: Relevance
“…Iron oxide nanoparticles with peroxidase‐like activities have been experimentally used as catalysts for activation of H 2 O 2 in root canal treatment. [ 266 ] Compared with conventional dental antibacterial irrigants used for disinfecting root canals, an irrigating solution comprising the nanoparticle‐H 2 O 2 assemblies is capable of killing significantly more Entercoccus faecalis , a type of bacteria that is commonly located in infected root canals that fail to heal after root canal treatment.…”
Section: Metal‐based Nanocompoundsmentioning
confidence: 99%
“…Iron oxide nanoparticles with peroxidase‐like activities have been experimentally used as catalysts for activation of H 2 O 2 in root canal treatment. [ 266 ] Compared with conventional dental antibacterial irrigants used for disinfecting root canals, an irrigating solution comprising the nanoparticle‐H 2 O 2 assemblies is capable of killing significantly more Entercoccus faecalis , a type of bacteria that is commonly located in infected root canals that fail to heal after root canal treatment.…”
Section: Metal‐based Nanocompoundsmentioning
confidence: 99%
“…4 Despite these advances in metallurgy and design, around 10% to 50% of surfaces are not reached by these instruments. [5][6][7][8] Consequently irrigation plays a major role in the debridement of the areas not reached by mechanical conformation. 9 An ideal irrigation agent should be organic and able to dissolve necrotic tissue, bactericide, lubricant, biocompatible, nontoxic and non-caustic for periapical tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to 5.25% NaOCl, nano-MgO (5 mg/L) and chitosan NPs exhibited statistically significant long-term efficiency in the elimination of E. faecalis in the root canal system [57,58]. A previous study showed that the biomimetic iron oxide NPs with peroxidase-like activity enhanced antibacterial activity on root canal surfaces and in dentinal tubules [59].…”
Section: Antimicrobial Applications In Dentistrymentioning
confidence: 99%